Topiramate inhibits adjuvant-induced chronic orofacial inflammatory allodynia in the rat - Mohos, Violetta; Harmat, Máté; Kun, Jozsef; Aczél, Tímea; Zsidó, Balázs Zoltán; Kitka, Tamás; Farkas, Sándor; Pintér, Erika; Helyes, Zsuzsanna (Frontiers in Pharmacology, 2024)
Chronic orofacial pain disorders are common debilitating conditions, affecting the trigeminal system. Its underlying pathophysiological mechanisms are still unclear and the therapy is often unsatisfactory, therefore, preclinical models are crucial to identify the key mediators and novel treatment options. Complete Freund's adjuvant (CFA)-induced orofacial inflammatory allodynia/hyperalgesia is commonly used in rodents, but it has not been validated with currently used drugs. Here we tested the effects of the adjuvant analgesic/antiepileptic voltage-gated Na + channel blocker complex mechanism of action topiramate in comparison with the gold standard antimigraine serotonin 5-HT1B/D receptor agonist sumatriptan in this model. CFA was injected subcutaneously into the right whisker pad of male Sprague-Dawley rats (250-300 g), then mechanonociceptive threshold values were investigated with von Frey filaments (3, 5, and 7 days after CFA injection). Effects of topiramate (30 mg/kg per os) and sumatriptan (1 mg/kg subcutaneous) on the adjuvant-induced chronic inflammatory orofacial allodynia were investigated 60, 120, and 180 minutes after the treatments each day. To determine the optimal concentration for drug effect analysis, we tested the effects of two different CFA-concentrations (1 and 0.5 mg/mL) on mechanonociceptive thresholds. Both concentrations of CFA induced a chronic orofacial allodynia in 60% of all rats. Although, higher CFA concentration induced greater allodynia, much more stable threshold reduction was observed with the lower CFA concentration: on day 3 the thresholds decreased from 18.30 g to approximately 11 g (low) and 5 g (high), respectively, however a slight increase was observed in the case of higher CFA concentration (on days 5, 7, and 11). In all investigation days, topiramate showed significant anti-allodynic effect comparing the pre and post drug dose and comparing the vehicle treated to the drug treated groups. Sumatriptan also caused a significant threshold increase compared to pre dose thresholds (day 3) and also showed a slight anti-allodynic effect compared to the vehicle-treated group (day 3 and 5).In the present study CFA-induced chronic orofacial allodynia was reversed by topiramate in rats validating the model with the adjuvant analgesic. Other than establishing a validated orofacial painrelated syndrome model in rats, new ways are opened for the repurposing of topiramate.